COMPARATIVE ANALYSIS OF CHANGES IN THE MORPHOLOGICAL AND MORPHOMETRIC PARAMETERS OF THE PANCREAS IN 9-MONTH-OLD WHITE OUTBRED RATS UNDER THE INFLUENCE OF EXPERIMENTAL ALCOHOL INTOXICATION, COMPARED WITH THE CONTROL GROUP (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Background: Alcohol intoxication remains a major etiological factor contributing to structural and functional impairment of the pancreas due to its high sensitivity to toxic influences. Morphological and morphometric evaluation is essential for understanding the degree of tissue damage and adaptive changes under toxic conditions.Objective: To perform a comparative analysis of morphological and morphometric changes in the pancreas of 9-month-old white outbred rats under experimental alcohol intoxication versus a control group.
Keywords: Pancreas, alcohol intoxication, morphometry, acinus, exocrinocyte, endocrinocyte.